Ocrelizumab in a case of refractory chronic inflammatory demyelinating polyneuropathy with anti‐rituximab antibodies. (8th November 2020) - Casertano, S.; Signoriello, E.; Rossi, F.; Di Pietro, A.; Tuccillo, F.; Bonavita, S.; Lus, G.
Abstract : Rituximab (RTX), a chimeric anti‐CD20 monoclonal antibody, has demonstrated good efficacy as treatment in patients with resistant chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), but it is highly immunogenic due to its structure. Ocrelizumab (OCR) is a humanized anti‐CD20 antibody, with higher tolerability and a lower immunogenic profile compared to RTX. We present a case of refractory CIDP effectively treated with OCR, switched from RTX after the development of anti‐drug antibodies. A 25‐year‐old man was admitted to our clinic for the onset of distal upper and lower limb weakness and numbness, with electrodiagnostic criteria of CIDP. After several attempted standard CIDP treatments, RTX was introduced due to poor control of clinical relapses. Unfortunately, the patient developed a high anti‐drug antibody titer after RTX infusion, with no control of disease. OCR was started as an off‐label treatment, resulting in partial recovery from the last recurrence and achieving good prevention of new relapses with no adverse events. We suggest that OCR should be considered as another therapeutic option in refractory CIDP. In the literature, this is the first case of CIDP treated with OCR, demonstrating good efficacy for its anti‐CD20 effect and better tolerability because of its lower immunogenicity. Abstract : Rituximab has demonstrated efficacy in resistant chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), but it is immunogenic due to its structure. Ocrelizumab is a new humanized anti‐CD20 antibody, with higher tolerability and a lower immunogenic profile compared to rituximab. Ocrelizumab should be considered as another therapeutic option in refractory CIDP.